The Use Of Irrational Drug On Antibiotics And Off-Label Drugs From Industry Perspective:Article Review - IRMA RAHAYU LATARISSA; Norisca Aliza Putriana (Fakultas Farmasi, Universitas Padjadjaran, 2018)
The World Health Organization (WHO) estimates that approximately 50% of all drug use is not appropriate in prescribing, preparing and selling. The inappropriate use of drugs will cause many problems. These issues include aspects of effectiveness, side effects, interactions, and economics. Rational use of drugs according to the WHO conference in Nairobi in 1985: when the patient receives treatment as clinical needed, dose as needed, time period was right, and a cost affordable to the patient's condition. Some cases of irrational use of drugs occur in the use of antibiotics and off-label drugs. One cause of irrational drug use is due to the cooperation between doctors as prescribing and pharmaceutical industry as a producer. In the pharmaceutical industry perspective, this will have an impact on the pharmaceutical profit industry, nowadays in Indonesia pay more attention to rational use of drugs (the right price indicator), supported by the current pharmaceutical era of health care shifted from money oriented or drug oriented to patient oriented.